Certificateless multi-source elliptic curve ring signcryption for cloud computing. (May 2023) - Yu, Huifang; Liu, Junze; Wang, Zhicang
Abstract: Network coding can encode and forward the received data packets to save the network resources and improve the bandwidth utilization in cloud computing environment. To resist the pollution attacks and improve the computational efficiency in network coding, we construct certificateless multi-source elliptic curve ring signcryption (CL-MSECRSC) scheme suitable for cloud computing, its security relies on the hardness of elliptic curve discrete logarithm (ECDL) and elliptic curve computation Diffie-Hellman (ECCDH) problems. CL-MSECRSC has the properties of anti-forgery, anti-pollution, confidentiality and unconditional anonymity; also, scalar multiplication operations greatly save its computation overhead.